Relatório de Estágio Profissional - Equipa de Infantis masculinos de Andebol do Futebol Clube do Porto/Dragon Force - Rafael Leite Ribeiro (2016)
The present report aims to describe the stages resulting from the vocational internship on Futebol Clube Porto/Dragon Force, season 2015-2016. Futebol Clube do Porto has the fundamental mission to train young talents in several modalities, seeking to competitive teams in different levels of training The company's organization structure offers to its collaborators all the conditions to conduct a competent work. The internship lasted for eleven months and aimed to follow the infant male team as head coach. Moreover, during this period it was necessary to perform extra activities besides training and game preparation. Therefore, this report is divided into several chapters: professional practice framework, methodologies and strategies and conclusions. In summary, this season was fascinating, and allowed me to acquire new professional and personal skills and support the dream of being a handball professional team head coach, one day.